Aplikasi Metode Resistivitas 2D untuk Menentukan Intrusi Air Laut di Lambada Lhok Aceh Besar Aceh - Gartika Setiya Nugraha; Marwan Marwan; Akmal Muhni (Jurnal Teknosains, 2019)
Lambada Lhok is one of the coastal areas with the most severe water crisis in Aceh Besar, Aceh. Clean water crisis happening in the area because of their breach of saltwater into freshwater aquifers and also due to the large decrease in ground water level that resulted in seawater intrusion. This research was conducted on four lines at two locations, namely: 3 (three) lines in the village of Lambada Lhok and 1 (one) line in the village of Kajhu. Kajhu village was used as comparative data for areas that are free from the intrusion of sea water. The research method using 2D resistivity Wenner-Schlumberger configuration, while the data acquisition using the ARES equipment. Data analysis using Res2Dinv software to make 2-dimension (2-D) cross section model. Lambada Lhok village is an alluvial deposition with an average height of 0-5 meters above sea level (dpl). The subsurface lithology of the village lambada lhok consists of clay sand, sandy clay and clay. Based on the results of the analysis of resistivity values indicate that the suspected sea water intrusion in the village of Lambada Lhok reaches a depth of 29 meters. It can be concluded that the spread of sea water intrusion in Lambada Lhok beginning of the line LL 1, LL 2 to LL 3. Distribution of seawater intrusion are most severe in the trajectory LL 2 and began to decrease at LL 3 trajectory.